Efektifitas Terapi Musik Religi terhadap Nyeri pada Pasien Fraktur - Sitti Muhsinah (Health Information : Jurnal Penelitian, 2020)
The main complaint of fracture patients is pain. Religious music therapy is a complementary non-pharmacological intervention to reduce pain. Music through a spiritual approach turns unpleasant experiences into meaningful experiences. This study purposed to determine the effect of religious music therapy on pain in fracture patients in Kendari City. Method used a quasi-experimental research design with pre and post-test control group, using consecutive sampling. Respondents were 32 people and 16 respondents each as the control and intervention groups. The results showed that there was a significant effect on decreasing the pain scale in the intervention group. In conclusion, religious music therapy is one of the non-pharmacological alternative interventions to reduce pain in fracture patients.